2009
DOI: 10.3168/jds.2009-2561
|View full text |Cite
|
Sign up to set email alerts
|

Hot topic: Sonication increases the heat stability of whey proteins

Abstract: The thickening or gelling of protein-based dairy streams and ingredients upon exposure to heat has been an ongoing problem in dairy processing for many decades. This phenomenon can restrict the range of dairy product options and reduce manufacturing efficiencies by limiting the type and extent of heat treatment that can be used. In this report, we outline a novel approach to overcoming this problem. The use of preheating treatments to induce whey protein aggregate formation in whey products is well known in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(68 citation statements)
references
References 14 publications
(13 reference statements)
6
61
0
1
Order By: Relevance
“…[16,17] The physical effects generated during acoustic cavitation are also used in therapeutic medicine, extraction and in modifying the functional properties of proteins. [18][19][20] Owing to a large number of applications in areas that include chemistry, physics, medicine, and so on, an understanding of the spatial distribution of the cavitation field is important in order to control and achieve maximum efficiency in the above mentioned applications. For example, a relatively uniform distribution of the cavitation bubbles in a liquid may be required to maximize the number of active bubbles and hence the amount of reactive radicals for the reduction/oxidation reactions mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] The physical effects generated during acoustic cavitation are also used in therapeutic medicine, extraction and in modifying the functional properties of proteins. [18][19][20] Owing to a large number of applications in areas that include chemistry, physics, medicine, and so on, an understanding of the spatial distribution of the cavitation field is important in order to control and achieve maximum efficiency in the above mentioned applications. For example, a relatively uniform distribution of the cavitation bubbles in a liquid may be required to maximize the number of active bubbles and hence the amount of reactive radicals for the reduction/oxidation reactions mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%
“…During the manufacture of secondary dairy products, heat treatment results in further viscosity increases. Ashokkumar et al [9,10] and Zisu et al [117] outlined a novel approach to overcome this problem. The application of ultrasound for a very short duration after such a heating step breaks down these aggregates and prevents their reformation on subsequent heating, thereby reducing the viscosity increase that is usually associated with this process (Fig.…”
Section: Whey Proteinsmentioning
confidence: 98%
“…It has been shown that ultrasound-induced benefits for various applications in dairy processing can be achieved within the first few seconds of ultrasound application [9,10]. With the availability of continuous flowthrough systems (Prosonix, CA & Hielscher Ultrasonics, Germany), the contact time of product with the acoustic field and sonotrode surfaces can be minimised.…”
Section: Formation Of Metal Particulatesmentioning
confidence: 99%
“…Radicals formed by the cleavage of biopolymers also have the potential to recombine into novel polymer structures [4]. The efficiency of HIUS for reducing the particle size of biopolymer solutions has already been proved by many authors [5][6][7][8][9][10][11][12][13][14][15][16][17]. Nowadays, the development of biopolymer nanoparticles has a particular importance for the design of food-grade delivery systems to encapsulate, protect and deliver bioactive components.…”
Section: Introductionmentioning
confidence: 99%